1999
DOI: 10.1159/000013497
|View full text |Cite
|
Sign up to set email alerts
|

IgA-Antigliadin Antibodies in Patients with IgA Nephropathy: The Secondary Phenomenon?

Abstract: Circulating IgA-antigliadin antibodies (IgA-AGA) are often found in patients with IgA nephropathy (NP). IgA-AGA are sensitive markers of an abnormal immune system reaction to gluten, seen particularly in patients with celiac disease. However, a lack of IgA-antireticulin and IgA-antiendomysium antibodies and often jejunal mucosal atrophy of patients with IgA NP suggest that most patients do not have latent celiac disease. To examine the relationship between IgA-AGA and clinical data, enzyme-linked immunosorbent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 41 publications
1
19
0
1
Order By: Relevance
“…The raised VV binding of total serum IgA1 in IgAN is probably a consequence of an increased proportion of circulating mucosal-type IgA1 antibodies in these patients. Our previous published study of this group of patients with IgAN showed that their serum levels of IgA1 anti-HP are higher than those of control subjects (18), and other groups have demonstrated the same for other mucosal antigens (38,39).…”
Section: Discussionsupporting
confidence: 49%
“…The raised VV binding of total serum IgA1 in IgAN is probably a consequence of an increased proportion of circulating mucosal-type IgA1 antibodies in these patients. Our previous published study of this group of patients with IgAN showed that their serum levels of IgA1 anti-HP are higher than those of control subjects (18), and other groups have demonstrated the same for other mucosal antigens (38,39).…”
Section: Discussionsupporting
confidence: 49%
“…Circulating T cells display increased activation and cytokine production (31-36), and there is persistent systemic overproduction of pIgA1 against a variety of systemic and mucosal antigens (37)(38)(39), but this is associated with a failure of affinity maturation of serum IgA antibodies (40). In the mucosa, subclinical intestinal inflammation is found in IgAN (41,42), but mucosal pIgA1 plasma cell numbers (42,43) and mucosally secreted IgA antibody responses (44) are reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Ots et al (24) found elevated IgA-AGA in about 50% of the patients with IgAN, which in Ots' study was also correlated to age, disease duration and blood pressure. Contradictory findings have however been described by others.…”
Section: Discussionmentioning
confidence: 77%
“…Although several studies have shown an increased frequency of serologic markers of coeliac disease in IgA-nephropathy, the substantiation of a correlation between IgA nephropaty and verified celiac disease has been inadequate except for a recent study from Collin P et al (24,25). The evidence of a role for other food antigens has been debated but is still unclear (6).…”
Section: Introductionmentioning
confidence: 99%